(untitled) (Environment & Health, 2022)
Objective: The aim of the work is to develop approaches to improving the information and analytical support for monitoring epidemiological studies and infectious diseases in the activities of public health institutions. Materials and methods: The studies were carried out on the basis of a retrospective review of long-term monitoring of epidemiological observations of infectious morbidity and indicators of microbiological and chemical pollution of environmental factors, performed by the state institution «Kirovohrad Regional Center for Disease Control and Prevention of the Ministry of Health of Ukraine». In this case, the following methods were used: dialectical - to determine the essence of information and analytical support for the activities of public health institutions; functional, comparative analysis - to analyze the activities of the state institution "Kirovohrad Regional Center for Disease Control and Prevention of the Ministry of Health of Ukraine"; model, integrated approaches - to develop a model of information and analytical support for the activities of public health institutions and measures for its implementation in practice; methods of statistical analysis - to determine the characteristics of the study of environmental objects and the dynamics of infectious diseases in the population. Results: According to monitoring observations of environmental objects in medical institutions, preschool and general educational institutions, social security institutions of the Kirovohrad region for 2020, which included data from 4196 studies, it was found that almost 15% of them do not meet the requirements of regulatory documents. At the same time, microbiological studies included 1207 samples and measurements, of which 117 samples (9.7%) were inappropriate, sanitary-chemical studies amounted to 2989 samples, of which 146 samples were inappropriate (4.9%) exceeding the permissible standards. The largest number of samples that do not comply with regulatory documents and pose a threat to human health were found in non-centralized water supply 77 samples. The analysis of the infectious morbidity of the population in the Kirovohrad region covered the period of 2018-2020, the dynamic review of which showed that, according to the criterion of general morbidity, the number of cases of infectious diseases is growing over time, while the incidence of infectious diseases in children tends to decrease. A number of shortcomings in accounting and data processing have been identified. Conclusions: The expediency of improving the methodological, software and technological support of the information and analytical direction of the functioning of the state institution "Kirovohrad Regional Center for Disease Control and Prevention of the Ministry of Health of Ukraine" is shown. This will improve the efficiency and quality of the implementation of monitoring studies, as well as the processing and analysis of the obtained data on the state of the environment and public health and the adoption of timely management decisions on its conservation.